Penerapan Metode Forecast dalam Menyusun Anggaran Penjualan Pupuk Non-Subsidi - Syamsul; Jenny Theresia Dewanto; Nurlailah (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The purpose of this study was to determine the most appropriate forecasting method to be applied in the preparation of the sales budget for non-subsidized Urea and NPK fertilizers in CV. Prima Tani. This study compares the qualitative method in the form of employee opinions and the quantitative method using the moment and least square methods. The type of research used is descriptive research with a quantitative approach. The result shows that sales forecasting using qualitative methods (employees' opinions) has a forecast error of 172,858 for Urea fertilizers and 235,656 for NPK fertilizers. Meanwhile, the results of sales forecasting using quantitative methods, namely the moment method and the least square method, obtained the same forecasting error value of 45,703 kilograms for Urea fertilizer and 110,880 for NPK fertilizer. So that the application of the quantitative method is more appropriate, because it has a smaller forecast error value and is closest to the actual sales value. However, the least square method is better to apply because the calculations are easier and simpler.